2023
DOI: 10.21203/rs.3.rs-2668086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral frailty among dentate and edentate older adults in long-term care

Abstract: Background: The objectives of this study were to compare oral frailty (OFr) among edentate and dentate older adults living in long-term care facilities (LTCF) and to clarify how edentulism and oral disease burden (ODB) of dentate older adults are associated with OFr. Methods: The population of this study comprised 94 edentate and 209 dentate residents in LTCF in Helsinki, Finland, who had previously participated in a nutritional study. The participants underwent a clinical oral examination. The dentate residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Risk factors for ROHD Systemic factors 16,17,19,20,[22][23][24]26,27 Oral factors 19 Socioeconomic factors 20,21,27 Attributes related to ROHD Frailty 16,17,21,27 Malnutrition 17,18,21,23,25,27 Oral Frailty 19,21,27 Oral health related factors [16][17][18][19][20][22][23][24][25][26][27] Challenges encountered in management of ROHD Problems related to older adults 17,19 Problems related to nursing staff 16,17,19 Challenges in individualizing dental treatment plans 16 oral conditions such as xerostomia, hyposalivation, microbiota as well as level of oral self-care and oral frailty. Attributes related to ROHD comprised of frailty, malnutrition, oral frailty and oral conditions encountered.…”
Section: Main Themes Sub-themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for ROHD Systemic factors 16,17,19,20,[22][23][24]26,27 Oral factors 19 Socioeconomic factors 20,21,27 Attributes related to ROHD Frailty 16,17,21,27 Malnutrition 17,18,21,23,25,27 Oral Frailty 19,21,27 Oral health related factors [16][17][18][19][20][22][23][24][25][26][27] Challenges encountered in management of ROHD Problems related to older adults 17,19 Problems related to nursing staff 16,17,19 Challenges in individualizing dental treatment plans 16 oral conditions such as xerostomia, hyposalivation, microbiota as well as level of oral self-care and oral frailty. Attributes related to ROHD comprised of frailty, malnutrition, oral frailty and oral conditions encountered.…”
Section: Main Themes Sub-themesmentioning
confidence: 99%
“…One of the included studies suggested that protection against OFr may come from maintaining one's natural teeth, maintaining good oral health throughout one's life, and preventing oral illnesses. 27 Management approaches for ROHD in older adults Institutionalized older adults need assistance in doing oral hygiene activities 17 and usage of various oral hygiene aids such as adaptive toothbrush handles, collis-curve brushes, triple-headed toothbrushes, water flossers, interdental brushes of different diameters, floss holders/single-use floss picks, and other oral hygiene products like electric toothbrushes help these people remove plaque more effectively and help with physical adaptations. 6,9 Among other potential approaches to manage ROHD in older adults, the need for specific dental protocols to be followed in residential care institutions along with training for nursing staff to cater to oral health maintenance and empowering caregivers in identifying oral pain-related signs were highlighted in the included articles.…”
Section: Main Themes Sub-themesmentioning
confidence: 99%